Grout Materials

By using TiO2 and P2O5 in the fine powder, the grout material maintains fluidity and prevents separation, addressing the issue of material separation in narrow gaps.

JP7602675B1Active Publication Date: 2024-12-18DENKA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024008217
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-01-23
Publication Date
2024-12-18
Estimated Expiration
2044-01-23

AI Technical Summary

Technical Problem

Existing grout materials with high fluidity tend to suffer from material separation when filling narrow gaps.

Method used

Incorporating TiO2 and P2O5 as chemical components in fine powder, along with a foaming substance and water reducing agent, to enhance thixotropic properties and prevent separation while maintaining fluidity.

Benefits of technology

The grout material achieves good fluidity and reduces material separation, ensuring effective filling of narrow gaps.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602675000001
    Figure 0007602675000001
Patent Text Reader

Abstract

To provide a grout material which has good fluidity and is less susceptible to material separation. [Solution] The fine powder that has passed through a sieve with 90 μm mesh is a grout material containing TiO2 as a chemical component, and it is preferable that the fine powder contains 0.03 mass% or more of TiO2 as a chemical component.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to grout materials. [Background technology]

[0002] Cement-based grout materials used in the civil engineering and construction fields are generally made by adding a water reducing agent to cement. Calcium sulfoaluminate-based expanding materials, lime-based expanding materials, and foaming agents such as aluminum powder are further added as necessary to make non-shrinkage materials, and these are mixed with river sand or silica sand, and are widely used to fill small gaps in concrete structures, gaps in upside-down construction, repair and reinforcement areas of structures, and under the base plates of machinery and equipment, under track floor plates, etc.

[0003] When filling voids with grout materials, for example, when filling relatively wide voids of 10 cm or more directly, a certain degree of fluidity is sufficient. However, when filling narrower gaps, such as voids of a few centimeters, a higher fluidity is required.

[0004] For example, Patent Document 1 discloses that a grout material containing aggregate and a binder containing cement and a specified expansive material provides good fluidity and high durability. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 11-130505 Summary of the Invention [Problem to be solved by the invention]

[0006] However, when a highly fluid grout material such as that described in Patent Document 1 is used, there is a problem in that the material is easily separated.

[0007] In view of the above, an object of the present invention is to provide a grout material that has good fluidity and is less susceptible to material separation. [Means for solving the problem]

[0008] As a result of intensive research aimed at solving the above problems, the present inventors have come up with the following invention and found that the above problems can be solved.

[0009] [1] A grout material in the form of fine powder that has passed through a 90 μm mesh sieve and contains TiO2 as a chemical component. [2] The grout material according to [1], wherein the fine powder contains TiO2 at 0.03 mass% or more as a chemical component. [3] A grout material according to [1] or [2], wherein the TiO2 content as a chemical component of the coarse powder that does not pass through a sieve with a mesh size of 90 μm is less than the TiO2 content as a chemical component of the fine powder. [4] The grout material according to any one of [1] to [3], wherein the fine powder contains 0.05 to 5 mass % of P2O5 as a chemical component. [5] The grout material according to any one of [1] to [4], wherein the fine powder contains 10 to 40 mass % of particles having a particle diameter of 5 μm or less. [6] A grout material according to any one of [1] to [5], containing a foaming substance and / or a water reducing agent. Effect of the Invention

[0010] According to the present invention, it is possible to provide a grout material that has good fluidity and is less susceptible to material separation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, one embodiment of the present invention (hereinafter, may be referred to as "this embodiment") will be described. In this specification, "parts" and "%" are based on mass unless otherwise specified.

[0012] The grout material according to this embodiment is a grout material in which fine powder passing through a sieve with 90 μm openings contains TiO2 as a chemical component. By containing TiO2 as a chemical component in the fine powder, it is possible to impart thixotropy when used as a grout material, and it is possible to make it difficult for material separation to occur while exhibiting good filling properties.

[0013] In addition, since fine powders with a sieve size of 90 μm or less have a relatively high initial reactivity, it is presumed that the inclusion of a certain amount of TiO2 in the fine powder makes it easier for the function of TiO2, i.e., the above-mentioned thixotropy, to be exerted.

[0014] From the viewpoint of better exerting thixotropy, the fine powder passed through a sieve with an opening of 90 μm preferably contains 0.03 mass % or more of TiO2 as a chemical component, more preferably 0.03 to 5 mass %, and even more preferably 0.05 to 3 mass %. In order to contain 0.03 mass % or more of TiO2 as a chemical component, a material containing TiO2 (for example, titanium oxide) may be used as the material.

[0015] In this embodiment, the TiO2 content as a chemical component of the coarse powder that did not pass through the sieve with 90 μm openings is preferably smaller than the TiO2 content as a chemical component of the fine powder. In other words, when the TiO2 content as a chemical component of the fine powder is larger than the TiO2 content of the coarse powder, the function of TiO2 in the highly reactive fine powder is easily exerted, and thixotropy is more easily imparted, making it possible to achieve good packing properties and to make it difficult for material separation to occur.

[0016] In order to more effectively exert the function of TiO2 in the fine powder, the ratio (B / A) of the TiO2 content (B) of the fine powder to the TiO2 content (A) of the coarse powder is preferably 1.1 to 100, and more preferably 1.5 to 55.

[0017] In the grout material according to the present embodiment, the fine powder passed through a sieve with an opening of 90 μm preferably contains 0.05 to 5 mass % of P2O5 as a chemical component, more preferably 0.08 to 3 mass %. By making the content of P2O5 0.05 to 5 mass %, it becomes easier to maintain the fluidity and to suppress flow-down, etc.

[0018] In order to include 0.05 to 5 mass % of P2O5 as a chemical component, a material containing P2O5 (for example, calcium phosphate) may be used.

[0019] In this embodiment, the P2O5 content as a chemical component of the coarse powder is preferably smaller than the P2O5 content as a chemical component of the fine powder. In other words, when the P2O5 content as a chemical component of the fine powder is larger than the P2O5 content of the coarse powder, the function of P2O5 in the highly reactive fine powder is more easily exhibited.

[0020] In order to more effectively exert the function of P2O5 in the fine powder, the ratio (D / C) of the P2O5 content (D) of the fine powder to the P2O5 content (C) of the coarse powder is preferably 1.1-100, more preferably 2-65.

[0021] The grout material of this embodiment preferably contains a foaming agent and / or a water reducing agent.

[0022] The foaming substance is used for the purpose of more effectively preventing the grout material from sinking or shrinking due to bleeding when the grout material is not yet hardened after application. The foaming substance is preferably a gas foaming substance that generates gas after being mixed with water.

[0023] Examples of the gas foaming substance include oily substances such as vegetable oils and mineral oils. Examples of the gas foaming substance include powder substances such as flaky aluminum powder surface-treated with stearic acid and aluminum powder produced by an atomizing method. Examples of the gas foaming substance include nitrogen gas foaming substances that foam nitrogen gas under an alkaline atmosphere, such as azo compounds, nitroso compounds, and hydrazine derivatives. Examples of the gas foaming substance include percarbonates such as sodium percarbonate, potassium percarbonate, and ammonium percarbonate, perborates such as sodium perborate and potassium perborate, permanganates such as sodium permanganate and potassium permanganate, and peroxides such as hydrogen peroxide.

[0024] As the gas foaming substance, it is preferable to use aluminum powder that has been surface-treated with stearic acid or the like, since this has a large effect of suppressing subsidence.

[0025] From the viewpoint of further suppressing bleeding, the content of the foaming substance in the grout material is preferably 0.0001 to 1%, more preferably 0.0005 to 0.5%, and even more preferably 0.001 to 0.2%.

[0026] The water reducer aids in the dispersion of each material and also serves to improve the fluidity of the mixed grout material.

[0027] The water reducing agent is not particularly limited, and examples thereof include naphthalene-based water reducing agents, melamine-based water reducing agents, aminosulfonic acid-based water reducing agents, and polycarboxylic acid-based water reducing agents, which can be used alone or in combination.

[0028] Specific examples of water reducing agents include naphthalene-based water reducing agents such as "Leobuild SP-9 Series" manufactured by NMB Corporation, "Mighty 2000 Series" manufactured by Kao Corporation, and "Sunflow HS-100" manufactured by Nippon Paper Industries Co., Ltd. Melamine-based water reducing agents such as "Sikament 1000 Series" manufactured by Sika Japan Co., Ltd. and "Sunflow HS-40" manufactured by Nippon Paper Industries Co., Ltd. Aminosulfonic acid-based water reducing agents such as "Paric FP-200 Series" manufactured by Fujisawa Pharmaceutical Co., Ltd. Polycarboxylic acid-based water reducing agents such as "Leobuild SP-8 Series" manufactured by NMB Corporation, "Darlex Super 100PHX" manufactured by Grace Chemicals Co., Ltd., and "Chupol HP-8 Series" and "Chupol HP-11 Series" manufactured by Takemoto Oil & Fat Co., Ltd.

[0029] Powdered water reducing agents are also available. Specifically, naphthalene-based water reducing agents include Kao Corporation's product name "Mighty 100", Sanyo Chemical Industries' product name "Sanyo Revlon P", and Daiichi Kogyo Seiyaku's product name "Cellflow 110P". Melamine-based water reducing agents include BASF Pozzolith's product name "Melment F10M". Polycarboxylic acid-based water reducing agents include Mitsubishi Chemical Corporation's product name "Queenflow 750" and Kao Corporation's product name "CAD9000P".

[0030] From the viewpoint of better fluidity, the content of the water reducing agent in the grout material is preferably 0.1 to 2% in terms of solid content, more preferably 0.2 to 1.8%, and even more preferably 0.3 to 1.0%.

[0031] In this embodiment, the fine powder that has passed through a sieve with an opening of 90 μm contains preferably 10 to 40 mass % of particles having a particle diameter of 5 μm or less, and more preferably 15 to 35 mass % of particles having a particle diameter of 5 μm or less. By containing 10 to 40 mass % of particles having a particle diameter of 5 μm or less, better thixotropy can be obtained.

[0032] In the grout material according to this embodiment, the fine powder that has passed through a sieve with an opening of 90 μm preferably contains, as chemical components, CaO, SiO2, Al2O3, and Fe2O3 in addition to the chemical components already described. The content of CaO is preferably 10 to 70 mass %, SiO2 is preferably 10 to 50 mass %, Al2O3 is preferably 1 to 20 mass %, and Fe2O3 is preferably 0.1 to 40 mass %.

[0033] The grout material according to this embodiment can be produced by, for example, mixing CaO raw material, Al2O3 raw material, Fe2O3 raw material, SiO2 raw material, TiO2 raw material, and optionally P2O5 raw material, firing the mixture to synthesize clinker, pulverizing the mixture using a ball mill, and then appropriately mixing fine aggregate, foaming material, water reducing agent, etc. For mixing, a mixing device such as a tilting mixer, an omni mixer, a Henschel mixer, a V-type mixer, or a Nauta mixer can be used.

[0034] As the fine aggregate, any fine aggregate that is commonly used can be used. Also, various admixtures can be mixed.

[0035] The content of the fine aggregate is preferably 50 to 350 parts by mass, more preferably 70 to 250 parts by mass, per 100 parts by mass of the cement component obtained by subtracting the fine aggregate from the grout material. By keeping the content of the fine aggregate within the above range, it is possible to improve the thick coating property.

[0036] The CaO raw material may be, for example, calcium oxide powder or limestone powder, the Al2O3 raw material may be, for example, aluminum oxide powder or bauxite powder, the Fe2O3 raw material may be, for example, iron oxide powder, the SiO2 raw material may be, for example, silicon dioxide powder or silica powder, the TiO2 raw material may be, for example, titanium oxide powder, and the P2O5 raw material may be, for example, calcium phosphate powder.

[0037] From the viewpoint of efficiently exerting its function, the content of the fine powder in the grout material is preferably 10 to 80 mass %, and more preferably 20 to 70 mass %.

[0038] The grout material of the present embodiment can be used by mixing with water. The amount of water to be mixed in this case is not particularly limited since it varies depending on the purpose and application of use and the content ratio of each material, but is preferably 10 to 70 parts, more preferably 14 to 65 parts, and even more preferably 16 to 60 parts, per 100 parts of grout material. By keeping the amount of water to be mixed at or above the lower limit, it is possible to suppress a decrease in fluidity and prevent the amount of heat generation from becoming extremely large. Also, by keeping the amount of water to or below the upper limit, it is possible to ensure strength development.

[0039] The method for mixing the grout material and water is not particularly limited, but it is preferable to use a hand mixer with a rotation speed of 900 rpm or more, a normal high-speed grout mixer, or a twin-shaft forced mixer.

[0040] When mixing with a hand mixer or high-speed grout mixer, it is preferable to first put a certain amount of water into a container such as a pail or a mixer, then add the grout mortar composition while rotating the mixer, and mix for 3 minutes or more.

[0041] In addition, in the case of mixing with a forced mixer, for example, the grout mortar composition is charged in advance into the mixer, and a predetermined amount of water is charged while rotating the mixer, and mixing is preferably carried out for at least four minutes.

[0042] The mixed grout material is usually pumped to the application site using a manual injection gun, a diaphragm hand pump, or a squeeze type mortar pump, and then filled and applied to become a hardened mass. EXAMPLES

[0043] (Materials used) ·CaO raw material: limestone powder ·Al2O3 raw material: bauxite powder Fe2O3 raw material: iron oxide powder ·SiO2 raw material: silica powder ·TiO2 raw material: titanium oxide powder ·P2O5 raw material: calcium phosphate powder Foaming material (gas foaming material): flaky aluminum powder with a surface treatment using stearic acid, commercially available product Water reducing agent: Naphthalene-based water reducing agent, "Cellflow 110P" manufactured by Daiichi Kogyo Seiyaku Co., Ltd. Water: Tap water

[0044] The CaO raw material, Al2O3 raw material, Fe2O3 raw material, SiO2 raw material, TiO2 raw material, and P2O5 raw material were mixed so that the chemical components of the fine and coarse powders were in the ratios shown in Table 1, and then calcined at 1,350°C to synthesize clinker. The clinker was then milled in a ball mill to a Blaine specific surface area of ​​3,500 cm. 2 / g to produce a cement component, and 100 parts by mass of the cement component were mixed with 200 parts by mass of fine aggregate, 45 parts by mass of water, 0.0025 parts by mass of gas foaming substance, and 0.5 parts by mass of a water reducing agent to produce a grout material.

[0045] The prepared grout material was sieved through a sieve with 90 μm openings, and the contents of chemical components in the fine powder that passed through and the coarse powder that remained on the sieve were measured. CaO, Al2O3, Fe2O3, and SiO2 were measured by X-ray fluorescence diffraction (XRF). TiO2, P2O5, etc. were also measured by X-ray fluorescence diffraction (XRF). In addition, the "other" components in the table are trace components such as SO3, MgO, Na2O, K2O, etc. The content of fine powder in the grout material was 35 mass%.

[0046] In addition, the ratio of particles having a particle diameter of 5 μm or less that were obtained by sieving a 5 μm mesh size among the fine powder that had passed through a sieve with a 90 μm mesh size was measured. The results are shown in Table 1.

[0047] The prepared grout material was evaluated for void ratio, bleeding amount, and fluidity in the following filling test. The results are shown in Table 1.

[0048] <Filling rate of filling test> Mortar (grout material) is poured into a box-shaped container 100cm long, 100cm wide, and 5cm high with a Φ4cm hole in the centre of each of two opposing sides through one of the holes. Pouring of the mortar is stopped when the mortar flows out of the other hole. After the mortar has hardened, the container is removed and the mortar filling rate is measured for the top 100cm x 100cm area. To measure the filling rate, prepare a 100cm x 100cm vinyl sheet and stick it on the top of the hardened body to mark the unfilled areas. The marked area is then cut away, and the weight of the vinyl leaving only the filled areas is measured and calculated using the formula below. Filling rate (%) = weight of vinyl in filled area (g) / total weight of vinyl (g) A high filling rate is preferable.

[0049] <Breeding rate> The bleeding rate (%) was calculated according to JSCE-F542. The lower the bleeding rate, the better the material separation resistance.

[0050] <Liquidity> In accordance with JSCE-F541, the J14 funnel flow rate was measured in a 30°C environment immediately after mixing (immediately after preparing the grout material) and 30 minutes later.

[0051] [Table 1] [Industrial Applicability]

[0052] The grout material of the present invention can be suitably used for filling small gaps in concrete structures, gaps in concrete structures formed by inverted pouring, repair or reinforcement of structures, and spaces under base plates of machinery and equipment, under track floor plates, etc.

Claims

1. A method for producing a powder containing a coarse powder that does not pass through a sieve with a mesh size of 90 μm and a fine powder that passes through a sieve with a mesh size of 90 μm, the fine powder that passed through the sieve with a mesh size of 90 μm being comprised of the following chemical components: CaO, SiO 2 , Al 2 O 3 , Fe 2 O 3 and TiO 2 The grout material contains 0.01 mass % or more of TiO 2 .

2. The fine powder has TiO as a chemical component. 2 The grout material according to claim 1, containing 0.03 mass% or more of

3. The coarse powder that did not pass through the sieve with a mesh size of 90 μm was found to contain TiO 2 The content of TiO as a chemical component of the fine powder 2 3. The grout material according to claim 1 or 2, wherein the content is less than 1.

0.

4. The fine powder contains P as a chemical component. 2 O 5 The grout material according to claim 1 or 2, containing 0.05 to 5 mass%.

5. The grout material according to claim 1 or 2, wherein the fine powder contains 10 to 40 mass% of particles having a particle diameter of 5 μm or less.

6. 3. The grout material according to claim 1 or 2, which contains a foaming agent and / or a water reducing agent.

Citation Information

Patent Citations

  • Preparation method of goaf filling slurry for mine

    CN107540303A

  • Anti-pulling type rigidity-controllable piled raft foundation structure and construction method

    CN113863349A

  • Grout composition for railway track

    JP1999130505A

  • Agent for improving ground consolidation and suspension type grout agent and ground improvement using the same

    JP1999349941A

  • Cement composition, mortar and cured body

    JP2022139528A